2010
DOI: 10.1534/genetics.110.120592
|View full text |Cite
|
Sign up to set email alerts
|

Promoter Strength Influences the S Phase Requirement for Establishment of Silencing at the Saccharomyces cerevisiae Silent Mating Type Loci

Abstract: In Saccharomyces cerevisiae, the two cryptic mating type loci, HML and HMR, are transcriptionally silent. Previous studies on the establishment of silencing at HMR identified a requirement for passage through S phase. However, the underlying mechanism for this requirement is still unknown. In contrast to HMR, we found that substantial silencing of HML could be established without passage through S phase. To understand this difference, we analyzed several chimeric HM loci and found that promoter strength determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 32 publications
1
11
2
Order By: Relevance
“…Independent experiments in which they exchanged the HML and HMR promoters, or introduced ectopic promoters at HML and HMR, convincingly demonstrated that promoter strength per se influences the dependence on cell cycle progression for the establishment of silencing (Ren et al 2010). Our result, indicating a decreased dependence on cell cycle progression at HML when we introduced an ectopic gene, is consistent with these results.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Independent experiments in which they exchanged the HML and HMR promoters, or introduced ectopic promoters at HML and HMR, convincingly demonstrated that promoter strength per se influences the dependence on cell cycle progression for the establishment of silencing (Ren et al 2010). Our result, indicating a decreased dependence on cell cycle progression at HML when we introduced an ectopic gene, is consistent with these results.…”
Section: Discussionsupporting
confidence: 88%
“…During the final review of this study, Ren et al (2010) published data also demonstrating that the HML locus is significantly less dependent on cell cycle progression for the establishment of silencing compared to HMR. Independent experiments in which they exchanged the HML and HMR promoters, or introduced ectopic promoters at HML and HMR, convincingly demonstrated that promoter strength per se influences the dependence on cell cycle progression for the establishment of silencing (Ren et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, silencing of a telomeric URA3 reporter occurred only during passage from M to G 1 phases (Martins-Taylor et al 2004;MartinsTaylor et al 2011). Finally, the a1 mating-type gene at HML was silenced in cells that were not cycling at all (Ren et al 2010;Lazarus and Holmes 2011). That the different reporter genes shut off in such different ways during establishment assays may indicate that the timing of silencing onset is regulated predominantly by the factors that perpetuate transcription of the genes, rather than the action of a silent chromatin-specific trigger.…”
Section: Silent Chromatin Establishment and The Cell Cyclementioning
confidence: 99%
“…As further discussed below, silencing of HMR requires passage through S phase (but not replication per se). However, "substantial silencing of HMLa" could be established without passage through S phase (Ren et al 2010). These authors attributed this difference in promoter strength-with the a1-a2 promoter being weaker than a1-a2-because HMRa is partially silenced without S phase, while HMLa requires S phase passage.…”
Section: Establishment and Maintenance Of Silencingmentioning
confidence: 99%